Cold atoms and molecules - Kajita, Masatoshi (IOP ebooks. 2020 collection., 2020)
This book introduces the preparation, measurement and properties of ultra-cold atoms and molecules at a level accessible to advanced undergraduate students or for researchers approaching the subject from different specialities. Including a review of cooling techniques, the book focuses on the behaviour and applications of both ultra-cold atoms and molecules, and how they are shaping research in atomic physics, quantum optics, condensed matter physics, statistical mechanics, quantum information processing, quantum simulators and finding applications in ultra-high-precision atomic clocks and quantum metrology. Readers of this book should develop an understanding of the techniques used to cool, trap, manipulate and perform measurements on ultra-cold atoms and molecules, as well as how such systems are in being used in a range of exciting areas of modern physics.